2007
DOI: 10.1039/b706747j
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear ruthenium(ii) complexes with flexible bridges as non-duplex DNA binding agents

Abstract: The stereoisomers of a series of dinuclear ruthenium(ii) complexes [{Ru(phen)(2)}(2)(micro-BL)](4+) (phen = 1,10-phenanthroline) with flexible bridging ligands (BL) bb2 {1,2-bis[4(4'-methyl-2,2'-bipyridyl)]ethane}, bb5 {1,5-bis[4(4'-methyl-2,2'-bipyridyl)]pentane}, bb7 {1,7-bis[4(4'-methyl-2,2'-bipyridyl)]heptane}, and bb10 {1,10-bis[4(4'-methyl-2,2'-bipyridyl)]decane} have been synthesised. Their binding to a control dodecanucleotide, d(CCGGAATTCCGG)(2), and a tridecanucleotide, d(CCGAGAATTCCGG)(2), which con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 35 publications
1
33
2
Order By: Relevance
“…However, other mechanisms, for example, modification of cell membrane function and cell adhesion, have been proposed. [11,43] In agreement with studies by Kelly and co-workers [44] and our own previous studies, [19] the results of our ITC experiments demonstrate that the dinuclear complexes have a moderately strong affinity for DNA. Furthermore, the results of this study indicate that the binding is entropically driven and enthalpically opposed.…”
Section: Mechanism Of Cell Deathsupporting
confidence: 93%
See 2 more Smart Citations
“…However, other mechanisms, for example, modification of cell membrane function and cell adhesion, have been proposed. [11,43] In agreement with studies by Kelly and co-workers [44] and our own previous studies, [19] the results of our ITC experiments demonstrate that the dinuclear complexes have a moderately strong affinity for DNA. Furthermore, the results of this study indicate that the binding is entropically driven and enthalpically opposed.…”
Section: Mechanism Of Cell Deathsupporting
confidence: 93%
“…[19,21] Tetraethylammonium chloride monohydrate, tetra-n-pentylammonium chloride, tetra-n-butylammonium chloride, tetrapropylammonium chloride, chloroquine diphosphate, ammonium chloride, chlorpromazine hydrochloride, filipin (from Streptomyces fulrissimus) and 5-(N,N-dimethyl) amiloride hydrochloride were purchased from Aldrich. Dimethyl sulfoxide (DMSO; biological grade), CT-DNA, procainamide hydrochloride, oligomycin A, 2-deoxy-d-glucose, bovine serum albumin (BSA) and sodium azide were purchased from Sigma.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the two metal centers are rigidly linked and consequently can not follow the curvature of the DNA, only one metal center may bind deeply to the DNA with the second metal center projecting out of the DNA [21][22][23][24][25][26][27][28][29][30][31][32][33][34]. The other kind of dinuclear Ru(II) complexes carrying a flexible chain should overcome the limitations and potentially allow both the metal centers to bind optimally to the DNA [35][36][37][38][39][40][41]. Since the chain length of the linker for dinuclear Ru(II) complexes has been reported to be a crucial factor in determining the binding efficiency [17], we have synthesized three novel dinuclear Ru (II) complexes with different lengths of flexible bridges as linkers of the two [Ru(bpy) 2 (pip)] 2+ {bpy = 2,2′-bipyridine; pip = 2-phenylimidazo [4,5-f] [1,10]phenanthroline}-based subunit [42], and studied their DNA binding properties.…”
Section: Introductionmentioning
confidence: 98%
“…Keywords: DNA · groove binding · luminescence · molecular recognition · ruthenium affinity through major-groove binding, [11] whereas Keene and collaborators have explored the application of optically resolved mono-and dinuclear Ru II complexes as minorgroove binding probes for canonical duplexes, mismatches, and hairpins. [12] In recent work, the Thomas and Otsuki groups have demonstrated that a dinuclear Ru II complex, which is structurally related to the minor-groove binder berenil, functions as a colorimetric sensor for DNA sequence and structure. [13] However, the effect of hydrogen-bonding moieties on the physical and biophysical properties of such systems is virtually unstudied.…”
Section: Introductionmentioning
confidence: 99%